Fabrication of optimized skin biomimics for improved interfacial retention of cosmetic emulsions. Issue 143 (27th June 2018) - Gkotsis, Georgios; Rickard, Jonathan James Stanley; Brooker, Anju; Bakalis, Serafim; Grover, Liam M.; Goldberg Oppenheimer, Pola
Abstract : Retention of hydrophobic active agents on human skin following the use of skin-care formulations is an important indication of the performance of the deposited product. We have developed a novel system which replicates the interaction between human skin and a cosmetic emulsion to systematically establish and characterize the key parameters driving the retention process at the interface. This included a comprehensive study of the skin's biology and physical properties which influenced the process, the fabrication of advanced, improved skin biomimics, the formulation of a cosmetic model-system emulsion, comprising a hydrophobic active agent i.e. petrolatum, commonly used in cosmetic products, the development of a dedicated and highly consistent deposition rig with a corresponding cleaning set-up and the systematic characterization of retention processes on the developed mimics. This study further explores the interplay of petrolatum with skin biomimics and studies the mechanisms that give rise to improved interfacial retention. Petrolatum has been found to create an occlusive layer on the skin mimic, displaying high coverage from emulsion formulations. The large particle size emulsions yielded improved retention on the developed skin biomimics due to the microstructure of the emulsion and the counter effect of the surfactant.